Probing Reconstituted Human Immune Systems in Mice With Oncogenic γ-Herpesvirus Infections - Münz, Christian (Frontiers in Immunology, 2020)
Mice with reconstituted human immune systems can mount cell-mediated immune responses against the human tumorviruses Epstein Barr virus (EBV) and Kaposi sarcoma associated herpesvirus (KSHV). Primarily cytotoxic lymphocytes protect the vast majority of persistently infected carriers of these tumorviruses from the respective malignancies for life. Thus, EBV and KSHV infection can teach us how this potent immune control is induced, what phenotype and functions characterize the protective lymphocyte compartments and if similar immune responses could be induced by vaccination. This review will summarize similarities and differences between EBV and KSHV associated pathologies and their immune control in patients and mice with reconstituted human immune systems. Furthermore, it will high-light which aspects of the near perfect immune control can be modelled in the latter preclinical animal models and discuss their relevance for cancer immunology in general.